Impact of intravascular ultrasound‐guided drug‐eluting stent implantation on patients with chronic kidney disease: Results from ULTIMATE trial. Issue 7 (22nd May 2019) - Zhang, Junjie; Gao, Xiaofei; Ge, Zhen; Han, Leng; Lu, Shu; Qian, Xuesong; Li, Qihua; Lu, Qinghua; Chen, Chonghao; Chen, Shao‐Liang
Abstract: Objectives: This study aimed to investigate the impacts of intravascular ultrasound (IVUS)‐guided drug‐eluting stent (DES) implantation on patients with chronic kidney disease (CKD) based on the ULTIMATE trial. Background: IVUS‐guided DES implantation improves clinical outcomes in complex lesions. However, routine IVUS guidance in patients with CKD remains controversial. Methods: CKD was defined as an estimated glomerular filtration rate (eGFR) <60 mL min −1 1.73 m −2 . The primary end point was target vessel failure (TVF) at 12 months, including cardiac death, target vessel myocardial infarction, and clinically driven target vessel revascularization. Results: eGFR was available in 1, 443 patients, of whom 723 were in the IVUS guidance group, and 720 were in the angiography guidance group. Finally, CKD was present in 349 (24.2%) patients. At 12 months, TVF in the CKD group was 7.2%, which was significantly higher than 3.2% in the non‐CKD group ( p = .001). Moreover, there were 25 TVFs in the CKD patients, with 7 (3.9%) TVFs in the IVUS group and 18 (10.7%) TVFs in the angiography group (hazard ratio [HR]: 0.35; 95% confidence interval [CI]: 0.15–0.84; p = .01), whereas 35 TVFs occurred in patients without CKD, with 14 (2.6%) TVFs in the IVUS group and 21 (3.8%) TVFs in the angiography group (HR: 0.67; 95% CI: 0.34–1.32; p = .25; p for interaction = .24). Conclusions: This study demonstrated that CKD patients undergoing DES implantations were associated with a higher risk of TVF at 12 months. More importantly, the risk of TVF in the CKD patients could be significantly decreased through IVUS guidance. Clinical Trial: NCT02215915.